2011
DOI: 10.1063/1.3555528
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on rectangular microhollow cathode discharge

Abstract: Rectangular microhollow cathode discharge in argon is investigated by using two-dimensional time-dependent self-consistent fluid model. The electric potential, electric field, particle density, and mean electron energy are calculated. The results show that hollow cathode effect can be onset in the present configuration, with strong electric field and high mean electron energy in the cathode fall while high density and quasineutral plasma in the negative glow. The potential well and electric filed reversal are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This finding indicates that a plasma potential well is formed at the discharge center. It is generally believed that formation of this potential well plays an important role in promoting discharge, and the HCE is more evident in this case [14,22]. However, in Model2, discharge occurs in the regime transitioning from Townsend discharge to the formation of the cathode sheath, as shown in figures 5(a) and (b).…”
Section: Different Characteristics Of Discharge In the Two Modelsmentioning
confidence: 89%
See 1 more Smart Citation
“…This finding indicates that a plasma potential well is formed at the discharge center. It is generally believed that formation of this potential well plays an important role in promoting discharge, and the HCE is more evident in this case [14,22]. However, in Model2, discharge occurs in the regime transitioning from Townsend discharge to the formation of the cathode sheath, as shown in figures 5(a) and (b).…”
Section: Different Characteristics Of Discharge In the Two Modelsmentioning
confidence: 89%
“…Therefore, the influence of metastable atoms on the discharge should be considered to allow the numerical models to approximate actual discharge characteristics. While several models without metastable atom involvement can provide a basic description of the characteristics of HCD [22,23]. However, how much difference between models with and without metastable atoms involvement has not been published in the previous work.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that this model can reproduce many features observed experimentally and allows one to understand pattern formation in DBDs [28][29][30][31] and dc glow discharges [17,18], formation and propagation of filamentary plasma arrays in high-power microwave breakdown at atmospheric pressure [32,33]. In [34], selforganized patterns on dc glow cathodes have been studied by means of a more realistic model of dc glows, which is in the spirit of models usually employed for detailed simulation of microdischarges in the absence of self-organization [35][36][37][38][39][40] and which accounts for two ionic species, several ionization channels, non-equilibrium population of excited states and comprises an energy equation for the electrons with appropriate boundary conditions (similar to those [41]). It was found that the effect of chemistry and non-locality of electron kinetic and transport coefficients does not cause qualitative changes in selforganization, which explains why the use of the basic model in simulations of self-organization has been successful.…”
Section: The Modelmentioning
confidence: 99%
“…BOEUF et al calculated the current-voltage (I ∼ V ) curve of MHCD and concluded that the discharge in MHCD transits from an abnormal discharge inside the hollow cathode to a normal glow discharge [6] . More work of numerical simulation also discussed the characteristics of MHCD, such as the effect of heating on gas [7] , the sustain discharge with a micro-hollow cathode [8] , self-pulsing phenomena [9] , the discharge of a limited cathode area [10] , and the electric field reversal in MHC [11] .…”
Section: Introductionmentioning
confidence: 99%